In Vitro Acitivities Test of Papaya Leaf Extract (Carica papaya. LINN) as an Antimalaria Agent - Johanis F Rehena (Jurnal ILMU DASAR, 2010)
Based on WHO’s estimation, there are at least 300-500 million people in the world infected by Malarian disease every year, 110 million people show the symptom, and 2.7 million people died. People who suffer from malaria in Kairatu regency are 1.296 people. Therefore, the invention of Malarian medicines is hoped to provide new medicine with mechanism and potential target and safe for the society. The objective of this study is to find out the role of extracted papaya’s leaf Cibinong and Solo Variety as antimalaria. The method is laboratory experimental, which is the sample of papaya’s leaf about 400 gram taken from Kairatu regency Maluku Province. Parasite used is Plasmodium falciparum strain G2300. antimalaria activity test in vitro is done toward the result of extracted papaya’s leaf dissolved in DMSO then it is done on flat titer with 24 holes. With level of parasitemia 1% and hematokrit 5%, and then is counted the percentage of parasitemia and growth percentage. Antimalaria test result on papaya’s leaf Cibinong variety with probit program show the value of IC50, 2.7821nanog/ml and Solo variety of Papaya is IC 50, 2.14279, in other word, that cibinong veriety and solo in vitro is active as an antimalaria.